Cooperative CO adsorption promotes high CO adsorption density over wide optimal nanopore range - Lei Chen; Takumi Watanabe; Hirofumi Kanoh; Kenji Hata; Tomonori Ohba (Adsorption Science & Technology)
Separation of CO 2 based on adsorption, absorption, and membrane techniques is a crucial technology necessary to address current global warming issues. Porous media are essential for all these approaches and understanding the nature of the porous structure is important for achieving highly efficient CO 2 adsorption. Porous carbon is considered to be a suitable porous media for investigating the fundamental mechanisms of CO 2 adsorption, because of its simple morphology and its availability in a wide range of well-defined pore sizes. In this study, we investigated the dependence of CO 2 adsorption on pore structures such as pore size, volume, and specific surface area. We also studied slit-shaped and cylindrical pore morphologies based on activated carbon fibers of 0.6–1.7 nm and carbon nanotubes of 1–5 nm, respectively, with relatively uniform structures. Porous media with larger specific surface areas gave higher CO 2 adsorption densities than those of media having larger pore volumes. Narrower pores gave higher adsorption densities because of deep adsorption potential wells. However, at a higher pressure CO 2 adsorption densities increased again in nanopores including micropores and small mesopores. The optimal pore size ranges of CO 2 adsorption in the slit-shaped and cylindrical carbon pores were 0.4–1.2 and 1.0–2.0 nm, respectively, although a high adsorption density was only expected for the narrow carbon nanopores from adsorption potentials. The wider nanopore ranges than expected nanopore ranges are reasonable when considering intermolecular interactions in addition to CO 2 –carbon pore interactions. Therefore, cooperative adsorption among CO 2 in relatively narrow nanopores can allow for high density and high capacity adsorption.